Chemical composition of sediments at various depths in core 710KH from campaign SO11 of R/V Sonne - Peter Stoffers; A Sioulas; Geoffrey P Glasby; Theo Thijssen (PANGAEA, 2023)
The chemical composition of sediments at various levels inside core 710KH also show a clear distinction between the overlying calcareous, siliceous-bearing to siliceous-rich muds and the underlaying dark brown clay. In particular, the dark brown clay is characterized by significantly higher contents of Mn, Fe, Co, Ni, Cu, Zn, Mg and P and lower contents of Ca and Ba than the overlying sediments. This distribution of elements probably reflects the presence of abundant micronodules, a lower content of barite and an almost complete absence of carbonate tests in the dark brown clays. The P content of the dark brown clays is higher than that of other typical deep-sea sediments from the equatorial N. Pacific or the SW Pacific. The organic-carbon content of the sediments is generally low and decreases from 0.3 to 0.1% with depth in the core.